(untitled) (Nordic Journal of African Studies, 2001)
The article is a humble contribution to our understanding of traditional African militaries by trying to discern the significance of firearms in the political-military decline of the Turkana community of Kenya. Before the nineteenth century, the Turkana had a large army and commanded such great respect among their pastoral neighbours that they always provided the paramount chief. Their army was tailored for pastoral raids and predatory expansion that suited their social and physical environment. However they encountered the British colonial army at a time they were experiencing a rivalry among their diviner-cum-military leaders. The community was devastated by colonial expeditions and a repressive system of administration that disarmed them and curtailed their tradition of reciprocal raids. In converse, their pastoral neighbours continued to arm and raid with impunity, as they were not under effective administration of either Ethiopia or Sudan. The situation has continued to the present day. In an area awash with automatic weapons the disadvantage to the Turkana community is clearly conspicuous.